Pengaruh Gaya Kepemimpinan Otoriter dan Lingkungan Kerja Terhadap Kinerja Pengrajin Batik di Kecamatan Tanjung Bumi melalui Motivasi Kerja Sebagai Variabel Intervening di Masa Pandemi Covid-19 - Achmad Bahruddin; Faidal Faidal (Jurnal Kajian Ilmu Manajemen (JKIM), 2021)
This study discusses the problems that exist in the Batik Business, Tanjung Bumi District, which are related to authoritarian leadership, work environment, and work motivation that can affect the performance of craftsmen. This study aims to examine the formulation of the problem. This study uses a quantitative approach, with a sample of 96 craftsmen. Data obtained from the interview process and distributing questionnaires to respondents, the data were analyzed using multiple regression with SPSS to answer the hypothesis. Based on the results of the analysis, partially authoritarian leadership and work environment variables have a positive and significant effect on work motivation with each tcount value of authoritarian leadership above 4.074 with a significant level of 0.000 0.2 and a work environment above 2.772 with a significant level of 0.007 0.2. The variables of authoritarian leadership, work environment, and work motivation have a positive and significant effect on the performance of craftsmen with each tcount value of authoritarian leadership above 1.338 with a significant level of 0.184 0.2, work environment above 4.931 with a significant level of 0.000 0.2, and motivation work above 1.616 with a significant level of 0.000 0.02. Based on the intervening regression analysis, it is known that authoritarian leadership and work environment have a positive and significant impact on performance through work motivation with an indirect coefficient of 0.087061 for authoritarian leadership and the results of the Sobel test with a t value of 2.4647066253 t table 0.67717 with a significant level of 0 ,2, and motivation of 0.047965 and the results of the Sobel test with a tcount of 2.5484676708 ttable 0.67717 with a significant level of 0.2.